Electrode and rechargeable lithium battery including same
By using carbon black compounds with specific specific surface area and crystallite size and nanofibrillated adhesives in the free-standing dry electrode membrane of rechargeable lithium batteries, the problem of poor nanofibrillation effect of the adhesive is solved, the mechanical and electrochemical properties of the electrode are improved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202510484619.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-17
- Filing Date
- 2025-04-17
- Publication Date
- 2025-10-24
AI Technical Summary
Existing rechargeable lithium battery electrodes have deficiencies in improving energy density and electrochemical performance, especially when using dry electrode films, where the nanofibrillation effect of the binder is poor, resulting in insufficient mechanical and electrical properties.
A free-standing dry electrode membrane is used, which contains a carbon black-based compound with a specific specific surface area and crystallite size as a conductive additive. The nanofibrillation of the binder is improved by flash lamp annealing treatment. Combined with binders such as polytetrafluoroethylene, electrodes with excellent mechanical and electrical properties are prepared.
The mechanical strength and electrochemical properties of the electrode are improved, the sheet resistance is reduced, and the reliability and overall performance of the battery are enhanced.
Smart Images

Figure CN120834141A_ABST
Abstract
Description
[0001] Cross Reference to Related Applications
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2024-0051523, filed on April 17, 2024, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. TECHNICAL FIELD
[0003] Aspects of embodiments of the present disclosure relate to an electrode for a rechargeable lithium battery and a rechargeable lithium battery including the same. BACKGROUND
[0004] As electronic devices using batteries, such as mobile phones, laptop computers, and electric vehicles, are rapidly spreading, the demand for rechargeable batteries having high energy density and high capacity is rapidly increasing. Accordingly, research and development for improving the performance of lithium ion rechargeable batteries are actively being conducted.
[0005] A rechargeable lithium battery is a battery including a cathode and an anode including an active material allowing intercalation and deintercalation of lithium ions, and an electrolyte, and generates electric energy through an oxidation-reduction reaction occurring when lithium ions are intercalated into and deintercalated from the cathode and the anode.
[0006] Recently, research on manufacturing an electrode including a dry electrode film not using a solvent is actively being conducted. The dry electrode film generally includes an electrode active material, a binder, a conductive additive, etc., and is manufactured in the form of a film.
[0007] The above information disclosed in technical background of the present invention is provided only for improving the understanding of the background of the present invention, and therefore can include information that does not constitute the prior art (related art). SUMMARY
[0008] According to aspects of embodiments of the present invention, an electrode including a dry electrode film in which nanofibrillation of a fibrillable binder is promoted and a rechargeable lithium battery including the same are provided.
[0009] However, aspects and objectives of the present invention are not limited to those mentioned above, and those of ordinary skill in the art will understand other aspects and objectives from the description of the present invention given below.
[0010] According to one or more embodiments of the present invention, the electrode includes a freestanding dry electrode film including an electrode active material, a binder, and a conductive additive, and the conductive additive includes a specific surface area of 350 m 2 / g or less and a crystallite size of 15 A or more.
[0011] In one or more embodiments, the specific surface area of the carbon black-based compound is in the range of 250 m 2 / g to 330 m 2 / g and the crystallite size of the carbon black-based compound is in the range of 15 A to 16 A.
[0012] In one or more embodiments, the carbon black-based compound is graphitized.
[0013] In one or more embodiments, the layers of the carbon black-based compound that are graphitized have a thickness of 1 nm or more.
[0014] In one or more embodiments, the pores of the carbon black-based compound have a diameter that is greater than 0 nm and less than or equal to 100 nm.
[0015] In one or more embodiments, 80% or more of all the pores in the carbon black-based compound include pores having a diameter in the range of 1 to 10 nm.
[0016] In one or more embodiments, the carbon black-based compound includes one or more of carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black.
[0017] In one or more embodiments, the carbon black-based compound is included in an amount of 90% by weight or more of the conductive additive.
[0018] In one or more embodiments, the binder is included in the dry electrode film in a fibrillated state.
[0019] In one or more embodiments, the binder includes polytetrafluoroethylene (PTFE), a polyolefin, or a mixture thereof.
[0020] In one or more embodiments, the electrode active material is a positive electrode active material or a negative electrode active material.
[0021] In one or more embodiments, the electrode active material includes lithium cobalt oxide.
[0022] In one or more embodiments, the carbon black-based compound is prepared by subjecting the carbon black-based compound to flash lamp annealing (FLA).
[0023] In one or more embodiments, the electrode is an electrode for a rechargeable lithium battery.
[0024] According to one or more embodiments, the rechargeable lithium battery includes an electrode according to an embodiment. BRIEF DESCRIPTION OF DRAWINGS
[0025] The following drawings attached to the present specification illustrate some example embodiments of the present application and, together with the detailed description given below, serve to provide a further understanding of the technical concept of the present application; however, the present application is not limited on the basis of the drawings.
[0026] Figures 1 to 4 is a schematic diagram showing a rechargeable lithium battery according to some embodiments.
[0027] Figures 5 to 7 Respectively show the results of transmission electron microscopy (TEM) analysis of the carbon black input to the dry electrode film of Example 1, Example 2 and Comparative Example 1.
[0028] Figure 8 Show the results of X-ray diffraction (XRD) analysis of the carbon black of the examples and comparative examples.
[0029] Figure 9 Show the results of crystallite size analysis of the carbon black of the examples and comparative examples.
[0030] Figure 10 Show the specific surface area of the carbon black of the examples and comparative examples.
[0031] Figure 11 Show the pore size distribution of the carbon black of the examples and comparative examples. In Figure 11 , ■ indicates Example 1, ▲ indicates Example 2, and ● indicates Comparative Example 1.
[0032] Figure 12 Show the results of storage modulus according to the measurement temperature of the dry electrode film of each of the examples and comparative examples. In Figure 12 , the single-dot chain line indicates Example 1, the dotted line indicates Example 2, and the solid line indicates Comparative Example 1.
[0033] Figure 13 Show the results of tensile strength and sheet resistance of the electrode of each of the examples and comparative examples.
[0034] Figure 14 and 15 Respectively show the results of rate performance of the battery including the electrode of each of the examples and comparative examples at 1C and 2C. In Figure 14 and 15 , the dotted line indicates Example 1, the single-dot chain line indicates Example 2, and the solid line indicates Comparative Example 1.
[0035] Figure 16 Show the results of ion resistance of the battery including the electrode of each of the examples and comparative examples.Figure 16 ■ indicates Example 1, ▲ indicates Example 2, and ● indicates Comparative Example 1.
[0036] Figure 17 Macmullin numbers of batteries including the electrodes of each of the examples and comparative examples are shown.
[0037] Figure 18 and 19 Results of life evaluation of batteries including the electrodes of each of the examples and comparative examples at 0.33 C and 1 C are shown, respectively. In Figure 18 and Figure 19 ■ indicates Example 1, ▲ indicates Example 2, and ● indicates Comparative Example 1. DETAILED DESCRIPTION
[0038] In this document, some example embodiments of the present application will be further described in detail with reference to the accompanying drawings. However, the terms or words used in the present specification and claims should not be interpreted as being limited to general or dictionary meanings, and should be interpreted in accordance with the concept of the present application based on the principles of the inventor's intention to best describe the principles of the present application with respect to a concept of a technical spirit of the present application. Therefore, the embodiments described herein and the configurations shown in the drawings are provided as some example embodiments of the present application, and do not necessarily represent all embodiments of the present application. Accordingly, it will be understood that there can be many equivalents and modifications of the embodiments which are within the scope of the present application as submitted.
[0039] Also, the expressions "include" and / or "comprise" used in the present specification indicate the presence of the mentioned shapes, numbers, steps, operations, components, elements, and / or sets thereof, but do not exclude the presence or addition of one or more other shapes, numbers, steps, operations, components, elements, and / or sets thereof.
[0040] Also, the drawings can not be drawn to scale and the size of some components can be exaggerated in order to facilitate understanding of the present application. Also, the same reference numerals can be assigned to the same components throughout the different embodiments.
[0041] When two objects are mentioned as "the same", it means that they are identical or substantially identical. Substantially identical can include the case of having a variation considered to be low in the art, for example, within 5%. Also, when a certain parameter is described as being uniform in a predetermined region, it can mean that the parameter is uniform from an average point of view.
[0042] Although terms such as "first" and "second" can be used to describe various components (constituents), the components (constituents) are not limited by such terms. The terms are used to distinguish one component (constituent) from another. Unless specifically set forth, the first component can also be the second component.
[0043] Throughout the specification, unless specifically stated otherwise, each component (constituent) can be singular or plural.
[0044] When any configuration is described as being disposed "on top of (or below) or "on (or below) a component, this can mean not only that the configuration is disposed in contact with the upper surface (or lower surface) of the component, but also that one or more other configurations can be interposed between the component and the configuration disposed on (or below) the component.
[0045] Further, when a component is described as being "connected", "coupled", or "linked" to another component, it will be understood that, although the components can be directly connected or linked to each other, one or more other components can be "interposed" between the two components, or the two components can be "connected", "coupled", or "linked" to each other through one or more other components. Further, when a part is described as being electrically connected to another part, this includes not only the case in which the two parts are directly connected, but also the case in which the two components are connected with one or more other devices interposed therebetween.
[0046] Throughout the specification, unless specifically stated otherwise, "A and / or B" means A, B, or A and B. That is, the term "and / or" includes any and all combinations of one or more of the associated listed items. Unless specifically stated otherwise, "C to D" means greater than or equal to C and less than or equal to D.
[0047] In the present specification, "specific surface area" can mean Brunauer, Emmett and Teller (BET) specific surface area.
[0048] In the present specification, "crystallite size" is used to evaluate the crystallinity of carbon black, and can be measured using the method described in the following evaluation method.
[0049] In the present specification, "storage modulus" can be measured for a dry electrode film using the method described in the following evaluation method.
[0050] In the present specification, "tensile strength (tensile strength)" can be measured using the method described in the following evaluation method.
[0051] The terms used in the present specification are used to describe embodiments of the present disclosure and are not intended to limit the present disclosure.
[0052] Electrode
[0053] The electrode according to embodiments can be a positive electrode or a negative electrode, depending on whether a positive electrode active material or a negative electrode active material including the following is used as an electrode active material.
[0054] According to embodiments, the electrode can be a positive electrode.
[0055] The electrode according to one or more embodiments includes a self-standing dry electrode film including an electrode active material, a binder, and a conductive additive, and the conductive additive includes a carbon black-based compound having a specific surface area of 350 m 2 / g or less and a crystallite size of 15 Å or more. The carbon black-based compound promotes nanofibrillation of the binder, and thus, can improve mechanical properties and electrical properties of a battery.
[0056] In embodiments, the dry electrode film can have a storage modulus of less than 300 MPa, for example, greater than or equal to 100 MPa and less than 300 MPa at 60℃. Within the above range, nanofibrillation of the fibrillatable binder is promoted, and thus, mechanical properties of the electrode film can be improved. In embodiments, the dry electrode film can have a storage modulus of greater than or equal to 100 MPa and less than 300 MPa, or in the range of 100 to 280 MPa at 60℃. Within the above range, mechanical properties of the electrode film can be improved even in a low content range of the fibrillatable binder, and the sheet resistance of the electrode film can also be reduced.
[0057] The dry electrode film can improve mechanical properties of the electrode by increasing the tensile strength of the electrode. The higher the tensile strength of the electrode, the lower the possibility that the aggregation (cohesion) of the electrode active material and the conductive additive caused by the binder can be broken, resulting in increased reliability of the battery.
[0058] In embodiments, the electrode can have a tensile strength of 0.4 MPa or more. In embodiments, the electrode can have a tensile strength of 0.5 MPa or more, for example, in the range of 0.5 MPa to 0.8 MPa. Within the above range, mechanical properties of the electrode can be improved and the sheet resistance can be reduced.
[0059] In embodiments, the self-standing dry electrode film is an electrode film in which an electrode powder including an electrode active material, a binder, and a conductive additive is manufactured in the form of a strip or a sheet having a certain (e.g., predetermined) thickness.
[0060] According to embodiments, the electrode active material can be a positive electrode active material.
[0061] As the positive active material, a compound capable of reversibly intercalating and deintercalating lithium (lithiated intercalation compound) can be used. In embodiments, one or more of a composite oxide of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof can be used.
[0062] The composite oxide can be a lithium transition metal composite oxide. Examples of the composite oxide can include a lithium nickel oxide, a lithium cobalt oxide, a lithium manganese oxide, a lithium iron phosphate compound, a lithium nickel manganese oxide not containing cobalt, or combinations thereof.
[0063] As examples, a compound represented by any one of the following chemical formulas can be used. Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b- c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NiG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G bO2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3(0≤f≤2); Li a FePO4(0.90≤a≤1.8).
[0064] In the above chemical formula, A is Ni, Co, Mn, or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; and L 1 is Mn, Al, or a combination thereof.
[0065] According to another embodiment, the electrode active material can be a negative electrode active material.
[0066] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and undoping lithium, or a transition metal oxide.
[0067] The material capable of reversibly intercalating / deintercalating lithium ions is a carbon-based negative electrode active material, and can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon can include graphite, such as natural graphite or artificial graphite, and examples of the amorphous carbon can include soft carbon, hard carbon, meso-phase pitch carbonizate, and calcined coke.
[0068] In an embodiment, a Si-based negative electrode active material or a Sn-based negative electrode active material can be used as the material capable of doping and undoping lithium. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiO x (0
[0069] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to an embodiment, the silicon-carbon composite can have a form including silicon particles and amorphous carbon coated on surfaces of the silicon particles.
[0070] In an embodiment, the silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer on surfaces of the core.
[0071] For example, the active material can be a positive electrode active material, such as lithium cobalt oxide.
[0072] The binder is not particularly limited, as long as the binder is fibrillated in the dry electrode film manufacturing step to be described below. Fibrillation can refer to the division of a polymer into fine fibers. Fibrillation can be performed using, for example, mechanical shearing force or the like. The surface of the fibrillated polymer fibers can be unraveled, and a plurality of fine fibers can be generated. The generated fine fibers can cause the electrode active material and / or the conductive additive to be described later to cohere to each other, thereby enabling the manufacture of a dry electrode film.
[0073] In embodiments, the binder can include polytetrafluoroethylene (PTFE), a polyolefin, or a mixture thereof. In embodiments, the binder can include PTFE, and in embodiments, can be PTFE. In embodiments, PTFE can be included in an amount of 60% by weight or more, for example, in an amount in the range of 90 to 100% by weight, based on the total weight of the binder.
[0074] In further embodiments, the binder can further include a non-fibrillatable binder. For example, the non-fibrillatable binder can include one or more of polyethylene oxide, polyvinylidene fluoride, and polyvinylidene fluoride-co-hexafluoropropylene.
[0075] In embodiments, the binder can be included in the dry electrode film in a fibrillated state.
[0076] In embodiments, the conductive additive includes a carbon black-based compound having a specific surface area of 350 m 2 / g or less and a crystallite size of 15 Å or more. By having a specific surface area of 350 m 2 / g or less and a crystallite size of 15 Å or more, the carbon black-based compound can promote the nanofibrillation of the fibrillatable binder by increasing adhesion with the fibrillatable binder. In particular, by having a crystallite size of 15 Å or more, the carbon black-based compound can promote nanofibrillation. Although the carbon black-based compound is originally in an amorphous state, by increasing the surface crystallinity of the carbon black-based compound, the carbon black-based compound can promote nanofibrillation of the fibrillatable binder, and the increased surface crystallinity can be reflected by the crystallite size of the carbon black-based compound.
[0077] In embodiments, the carbon black-based compound can have a specific surface area of, for example, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350 m 2 / g, 200 m 2 / g to 350 m 2surface area in the range of 200 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 250 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 270 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 280 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 290 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 300 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 310 m2 / g to 330 m2 / g. In embodiments, the carbon black-based compound can have a specific surface area in the range of 320 m2 / g to 330 m2 / g. 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m 2 / g to 330 m In the above ranges, nanofibrillation of the fibrillatable adhesive can be further promoted.
[0078] In embodiments, the carbon black-based compound can have a crystallite size in the range of, for example, 15, 15.1, 15.2, 15.3, 15.4, 15.5, 15.6, 15.7, 15.8, 15.9, 16, 16.1, 16.2, 16.3, 16.4, 16.5, 16.6, 16.7, 16.8, 16.9, 17, 17.1, 17.2, 17.3, 17.4, 17.5, 17.6, 17.7, 17.8, 17.9, 18, 18.1, 18.2, 18.3, 18.4, 18.5, 18.6, 18.7, 18.8, 18.9, 19, 19.1, 19.2, 19.3, 19.4, 19.5, 19.6, 19.7, 19.8, 19.9, 20 Å, 15 Å to 20 Å. In embodiments, the carbon black-based compound can have a crystallite size in the range of 15 Å to 17 Å. In embodiments, the carbon black-based compound can have a crystallite size in the range of 15 Å to 16 Å, 15.3 Å to 16 Å, 15.5 Å to 16 Å, or 15.7 Å to 15.9 Å. In the above ranges, nanofibrillation of the fibrillatable adhesive can be further promoted.
[0079] In embodiments, the carbon black-based compound can be graphitized, and its graphitized layers can have a thickness of 1 nm or more, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 nm, 1 to 10 nm.
[0080] The carbon black-based compound that satisfies both the specific surface area and the crystallite size can be prepared by a flash lamp annealing (FLA) process. Herein, the FLA will be described in further detail.
[0081] The FLA can graphitize and increase the crystallinity of the carbon black-based compound by irradiating the carbon black-based compound with light. In an embodiment, the FLA can be performed by irradiating the carbon black-based compound with light having an energy density in the range of 50 to 300 J / cm 2 In the above range, the specific surface area and the crystallite size can be easily satisfied.
[0082] In an embodiment, the FLA can be performed by irradiating the carbon black-based compound with light having an energy density in the range of 50-200 J / cm 2 In the above range, carbon black having a specific surface area in the range of 250 m 2 / g to 330 m 2 / g and a crystallite size in the range of 15 Å to 16 Å can be easily prepared.
[0083] The FLA can be performed under atmospheric conditions. In the above range, the specific surface area and the crystallite size can be easily satisfied.
[0084] In an embodiment, the pores of the carbon black-based compound can have a diameter greater than 0 nm and less than or equal to 100 nm.
[0085] In an embodiment, 80% or more, for example, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100% (based on the area ratio) of all the pores in the carbon black-based compound can include pores having a diameter in the range of 1 to 10 nm. This is implemented by the above FLA, and in the above range, the above effects of the dry electrode film can be easily achieved.
[0086] The carbon black-based compound can include one or more of carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black. In an embodiment, the carbon black-based compound can be carbon black.
[0087] In an embodiment, the carbon black-based compound can be included in an amount of 90% by weight or more of the conductive additive, for example, in an amount in the range of 95 to 100% by weight or an amount of 100% by weight. In the above range, an electrode having excellent electrical properties and mechanical properties can be manufactured.
[0088] In an embodiment, the carbon black-based compound can be included in an amount in the range of 0.1 to 5% by weight of the dry electrode film. Within the above range, the mechanical properties and electrical properties of the electrode can be improved. In an embodiment, the carbon black-based compound can be included in an amount in the range of 0.1 to 3% by weight, or 0.5 to 2% by weight.
[0089] In addition to the carbon black-based compound, the conductive additive can further include a conductive additive that is electrically conductive and does not cause chemical changes in the battery (herein, referred to as a "conductive additive other than the carbon black-based compound"). For example, the following can be used as the conductive additive other than the carbon black-based compound: graphite, such as natural graphite or artificial graphite; conductive fibers, such as carbon fibers or metal fibers; fluorinated carbon; metal powders, such as aluminum or nickel powders; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives, etc.
[0090] In an embodiment, in the free-standing dry electrode film, the electrode active material can be included in an amount in the range of 80 to 99% by weight, for example, 90 to 99% by weight, the binder can be included in an amount in the range of 0.5 to 20 or 19.5% by weight, for example, 0.5 to 10 or 9.5% by weight, and the conductive additive can be included in an amount in the range of 0.5 to 20 or 19.5% by weight, for example, 0.5 to 10 or 9.5% by weight. Within the above ranges, the dry electrode film can be easily manufactured, and there can be an effect of improving the electrochemical properties and mechanical strength of the electrode.
[0091] In an embodiment, the free-standing dry electrode film can be manufactured by the following steps:
[0092] (a) a process of preparing a powdery mixture including an electrode active material, a binder, and a conductive additive;
[0093] (b) a process of preparing a mixture mass by kneading the powdery mixture;
[0094] (c) a process of obtaining an electrode powder by pulverizing the mixture mass; and
[0095] (d) a process of obtaining a free-standing dry electrode film by calendering the electrode powder.
[0096] First, the electrode active material, the binder, and the conductive additive are mixed to prepare a powder mixture. The mixing is performed so that the electrode active material, the binder, and the conductive additive can be uniformly distributed in the mixture, and since the electrode active material, the binder, and the conductive additive are mixed in a powder form, the mixing is not limited as long as the electrode active material, the binder, and the conductive additive can be simply mixed. However, the mixture is used to manufacture a dry electrode film, and the mixture does not include a solvent. The mixing can be performed by dry mixing, for example, by inputting the materials into a device such as a blender.
[0097] In an embodiment, although the mixing time is not particularly limited, the mixing can be performed for 1 second to 10 minutes. In an embodiment, although the mixing speed is not particularly limited, the mixing speed can be appropriately controlled in the range of about 3,000 rpm to 30,000 rpm. As an example, for high uniformity and control of the crystallinity of the binder resin, the electrode active material, the binder, and the conductive additive can be mixed at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 5 minutes, for example, 2 minutes, and in an embodiment, at a speed of 10,000 rpm to 15,000 rpm for 30 seconds to 5 minutes, using a mixer to manufacture a dry electrode film.
[0098] Next, the above-obtained mixture is subjected to a kneading process for fibrillating the binder. The kneading is a step of forming a mixture mass of 100% by weight solid content by combining or connecting the electrode active material and / or the conductive additive while the binder is fibrillated.
[0099] In an embodiment, the kneading in step (b) can be controlled at a speed of 10 rpm to 100 rpm. For example, the kneading can be controlled at a speed of 40 rpm or more or 70 rpm or less within the above range. In an embodiment, the kneading can be performed for 1 minute to 30 minutes. For example, within the above range, the kneading can be performed at a speed of 40 rpm to 70 rpm for 3 minutes to 7 minutes. In an embodiment, in the kneading, the shear rate can be controlled in the range of 10 / s to 500 / s. In an embodiment of the present application, the kneading can be performed for 1 minute to 30 minutes, and the shear rate can be controlled in the range of 30 / s to 100 / s.
[0100] In an embodiment, the kneading step can be performed at a high temperature and a pressure higher than or equal to the atmospheric pressure. In an embodiment, the kneading step can be performed at a pressure higher than the atmospheric pressure. In an embodiment, the kneading can be performed at a temperature in the range of 70°C to 200°C, and in an embodiment, 90°C to 150°C.
[0101] In an embodiment, the kneading can be performed at a pressure higher than or equal to normal pressure, and in an embodiment, at a pressure in the range of 1 atm to 3 atm, and in an embodiment, at a pressure in the range of 1.1 atm to 3 atm. If the kneading is performed at an excessively high pressure and shear force deviating from the above range, the excessive shear force and pressure can cause the formed fibers to be cut, or the density of the mixture mass can be too high. That is, according to the present application, if the low shear mixing process is performed at a high temperature and a pressure higher than or equal to normal pressure instead of performing the high shear mixing, the intended effects of the present application can be achieved.
[0102] Next, a process of obtaining an electrode powder by again pulverizing the mixture mass prepared by the kneading process is performed.
[0103] The mixture mass prepared by the kneading can be immediately calendered, but in this case, the mixture mass can need to be prepared in the form of a film by pressing at a strong pressure and a high temperature, and thus, a problem in which the density of the film excessively increases or a film having a uniform density cannot be obtained can occur. Therefore, according to an embodiment of the present application, the prepared mixture mass undergoes a pulverization step.
[0104] The pulverization is not limited, and can be performed using a known pulverization device such as a blender (stir cutter) or a grinder. In an embodiment of the present application, the pulverization speed can be controlled in the range of 3,000 rpm to 30,000 rpm. In an embodiment, the pulverization time can be controlled in the range of 1 second to 10 minutes. However, the pulverization speed and the pulverization time are not particularly limited to the above ranges. As an example, the pulverization can be performed at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, or at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 5 minutes. Within the above ranges, the pulverization can be sufficiently performed, thereby facilitating film formation and reducing the degree of generation of fine powder.
[0105] The electrode powder is heated and pressed to manufacture a dry electrode film. The electrode powder obtained by completing the pulverization process as above is fed into a calendering process.
[0106] The electrode powder is heated and pressed and processed into a sheet-type dry electrode film by the calendering process. The calendering process can be performed using a pair of calendering rolls facing each other. In an embodiment of the present application, the calendering process can be performed by a method in which the electrode powder passes between a plurality of calendering rolls.
[0107] The electrode powder can be pretreated before the calendering process is performed.
[0108] The pre-treatment process can be performed by a method in which heat is applied to the electrode powder to maintain the temperature of the powder at 80°C or higher, in embodiments at 100°C or higher, for a certain (e.g., predetermined) amount of time. In embodiments, the pre-treatment process can be performed for 1 minute or longer, and the pre-treatment process time can be appropriately adjusted depending on the amount of powder. For example, the temperature of the powder can be maintained at 80°C or higher for 1 minute or longer or can be maintained at 100°C or higher for 1 minute or longer. Alternatively, in order to prevent or substantially prevent deterioration (degradation) of the electrode components, e.g., the binder resin, included in the electrode powder, the heating temperature of the electrode powder can be controlled to be lower than the melting point of the binder resin. For example, the heating temperature of the electrode powder can be controlled to be lower than 320°C. The pre-treatment process can be performed using a commonly used heating device, e.g., a convection oven or an infrared heating device. Here, the electrode powder does not stagnate while being stirred and heated.
[0109] In embodiments of the present application, the dry electrode film can have a thickness in the range of 100 μm to 200 μm, but the thickness is not particularly limited thereto. For example, the dry electrode film can have a thickness in the range of 100 μm to 150 μm.
[0110] The electrode can further include a current collector.
[0111] The current collector is not particularly limited as long as the current collector provides high electrical conductivity and does not cause chemical changes in the battery. For example, the following can be used as the current collector: stainless steel, aluminum, nickel, titanium, calcined carbon, copper, copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, or a polymer substrate having a surface coated with an electrically conductive metal and treated with carbon, nickel, titanium, silver, or the like. In embodiments, the current collector can have irregularities (e.g., fine irregularities) formed on its surface to increase adhesion of the electrode active material, and can be in any one of a variety of forms such as a film, a sheet, a foil, a mesh, a porous body, a foamed body, and a nonwoven body. In embodiments of the present application, the current collector can have a thickness in the range of 10 μm to 50 μm, but the thickness is not particularly limited thereto. For example, the current collector can have a thickness in the range of 10 μm to 20 μm.
[0112] In embodiments, the electrode can include a current collector and a dry electrode film laminated on the current collector.
[0113] Rechargeable lithium battery
[0114] According to one or more embodiments, a rechargeable lithium battery is provided, wherein the rechargeable lithium battery includes an electrode according to embodiments of the present application.
[0115] In embodiments, the battery can include a cathode according to embodiments of the present application and an anode according to embodiments of the present application. In further embodiments, the battery can include a cathode or an anode according to embodiments of the present application.
[0116] The anode can be manufactured using a composition including the above-described anode active material. The anode active material can be the same as described above. The composition can further include a binder and / or a conductive agent. In embodiments, the anode can be manufactured by a wet method. The binder and the conductive agent can be selected from the general types known to those skilled in the art.
[0117] The cathode can be manufactured using a composition including the above-described cathode active material. The cathode active material can be the same as described above. The composition can further include a binder and / or a conductive agent. In embodiments, the above-described cathode can be manufactured by a wet method. The binder and the conductive agent can be selected from the general types known to those skilled in the art.
[0118] The rechargeable lithium battery can further include an electrolyte solution.
[0119] The rechargeable lithium battery can further include an electrolyte. The electrolyte for the rechargeable lithium battery includes a non-aqueous organic solvent and a lithium salt.
[0120] The non-aqueous organic solvent serves as a medium through which ions involved in electrochemical reactions of the battery can move.
[0121] The non-aqueous organic solvent can be a carbonate-based, ester-based, ether-based, ketone-based, or alcohol-based solvent, an aprotic solvent, or a combination thereof, and can be used individually or in combination of two or more.
[0122] In embodiments, if a carbonate-based solvent is used, a cyclic carbonate and a chain-based carbonate can be used in combination.
[0123] A separator (separator) can be present between the cathode and the anode depending on the type of the rechargeable lithium battery. The separator can include polyethylene, polypropylene, polyvinylidene fluoride, a multi-layer film of two or more layers thereof, and a mixed multi-layer film, such as any one of a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.
[0124] The separator can include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof on one or both surfaces of the porous substrate.
[0125] The porous substrate can be a film formed of any selected polymer, for example, polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyether sulfones, polyphenylene ethers, cyclic olefin copolymers, polyphenylene sulfides, polyethylene naphthalate, glass fibers, polytetrafluoroethylene (e.g., Teflon), or a copolymer or mixture of two or more thereof.
[0126] The organic material can include a polyvinylidene fluoride-based polymer or a (meth)acrylic polymer.
[0127] In an embodiment, the inorganic material can include inorganic particles of any one selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto.
[0128] The organic material and the inorganic material can be mixed in one coating layer, or coating layers including the organic material and coating layers including the inorganic material can be stacked.
[0129] The rechargeable lithium battery can be classified into any one of a cylindrical, a prismatic, a pouch, a coin-type battery, etc. depending on its shape. Figures 1 to 4 is a schematic diagram illustrating a rechargeable lithium battery according to some embodiments. Figure 1 illustrates a cylindrical battery; Figure 2 illustrates a prismatic battery; and Figure 3 and 4 illustrates a pouch-type battery. Referring to Figures 1 to 4 , the rechargeable lithium battery 100 can include an electrode assembly 40 including a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 can be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 can include a sealing member 60 sealing the case 50, as shown in Figure 1 . In an embodiment, as shown in Figure 2 , the rechargeable lithium battery 100 can include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in Figure 3 and 4 , the rechargeable lithium battery 100 can include an electrode tab 70, which can be, for example, a positive electrode tab 71 and a negative electrode tab 72, which serve as an electrical path for leading out the electric current formed in the electrode assembly 40 to the outside.
[0130] As non-limiting examples, the rechargeable lithium battery according to embodiments can be applied to automobiles, mobile phones, and / or various types of electrical equipment.
[0131] The rechargeable lithium battery described above can be used to manufacture a battery pack. The battery pack according to one or more embodiments of the present application includes an assembly of individually connected cells and a pack case to accommodate the same. The battery pack can further include components for electrical connection of the cells such as bus bars, a cooling unit, external terminals, etc.
[0132] The battery pack can be installed in, for example, a vehicle. For example, the vehicle can be an electric vehicle, a hybrid vehicle, or a plug-in hybrid vehicle. For example, the vehicle can be a four-wheeled vehicle or a two-wheeled vehicle. The vehicle according to embodiments of the present application includes the battery pack according to embodiments of the present application. The vehicle operates by receiving electric power from the battery pack according to embodiments of the present application.
[0133] Here, some embodiments and comparative examples of the present application will be described. However, the following embodiments are provided only as some examples of the present application, and the present application is not limited to the following embodiments.
[0134] Example 1
[0135] Flash lamp annealing (FLA) treatment of carbon black
[0136] FLA was performed on carbon black (amorphous, LITX66, Cabot) to modify the carbon black. The FLA was performed under atmospheric conditions and at an energy density of 80 J / cm 2 using a xenon lamp (PerkinElmer Corp., UK), a beam guiding reflector, and a pulse controller (Semisysco, Korea).
[0137] Manufacture of dry electrode film
[0138] 96.7% by weight of lithium cobalt oxide as a positive electrode active material, 1.8% by weight of polytetrafluoroethylene (PTFE) as a binder, and 1.5% by weight of modified carbon black were input into a blender and mixed at 10,000 rpm for 1 minute to obtain a mixture. Next, the obtained mixture was input into a kneader and kneaded at 110°C at a speed of 60 rpm for 5 minutes to obtain a mixture mass, and then the mixture mass was input into a blender and pulverized at 10,000 rpm for 60 seconds to obtain an electrode powder. Then, the electrode powder was repeatedly pressed using a calender roll (roll diameter: 200 mm, roll temperature: 80°C) to obtain a dry electrode film (thickness: 150 μm).
[0139] Manufacture of electrode
[0140] The manufactured dry electrode film was laminated on a carbon-coated aluminum current collector to manufacture an electrode.
[0141] Example 2
[0142] Flash lamp annealing (FLA) treatment of carbon black
[0143] The FLA was performed on carbon black (amorphous, LITX66, Cabot) to modify the carbon black. The FLA was performed under atmospheric conditions and at an energy density of 260 J / cm2using a xenon lamp (PerkinElmer Corp., UK), a beam guiding reflector, and a pulse controller (Semisysco, Korea). 2
[0144] Manufacture of dry electrode film and electrode
[0145] The modified carbon black was used to manufacture a dry electrode film and an electrode in the same manner as in Example 1.
[0146] Comparative Example 1
[0147] A dry electrode film and an electrode were manufactured in the same manner as in Example 1 using carbon black (amorphous, LITX66, Cabot) without the flash lamp annealing treatment of Example 1.
[0148] The dry electrode films and the carbon black manufactured in the examples and the comparative example were evaluated for physical properties or less.
[0149] TEM analysis of carbon black
[0150] TEM analysis was performed on the carbon black of Example 1, Example 2, and Comparative Example 1. The degree of crystallinity of the carbon black can be evaluated by TEM analysis. The results thereof are shown in Figures 5 to 7 Figure 5 and 6 show TEM images of the carbon black subjected to the FLA in each of Example 1 and Example 2, and Figure 7 show TEM images of the amorphous carbon black.
[0151] As shown in Figure 5 and 6 , it can be confirmed that graphitization occurs on the surface of the carbon black. On the other hand, as shown in Figure 7 , it can be confirmed that graphitization does not occur on the surface of the carbon black.
[0152] XRD analysis of carbon black
[0153] XRD analysis was performed on the carbon black of Example 1, Example 2, and Comparative Example 1. The crystallinity of the carbon black can be analyzed by XRD analysis. The results thereof are shown in Figure 8 In Figure 8 , the solid line indicates Comparative Example 1, the dashed line indicates Example 1, and the single-dot chain line indicates Example 2.
[0154] As Figure 8 shown in Table 1 below and
[0155] Crystallite size analysis of carbon black
[0156] The crystallite size analysis was performed on the carbon black of Example 1, Example 2 and Comparative Example 1. The crystallite size was measured after XRD (Rigaku, SmartLab) analysis using the Scherrer equation. The results thereof are shown in Table 1 below and Figure 9 .
[0157] Specific surface area of carbon black
[0158] The specific surface area of carbon black was evaluated by BET analysis (Quantachrome, Autosorb IQ ). The results thereof are shown in Table 1 below and Figure 10 .
[0159] Pore size distribution of carbon black
[0160] The pore size distribution of carbon black was evaluated by BET analysis (Quantachrome, Autosorb IQ ). The results thereof are shown in Figure 11 .
[0161] Evaluation of storage modulus of dry electrode film
[0162] The storage modulus was obtained at each measurement temperature of the dry electrode film of the examples and comparative example. The storage modulus was measured by laminating (layering) a plurality of dry electrode films each having a thickness of 15 μm to make a sample having a thickness of 600 μm and a circular cross section having a diameter of 8 mm, raising the temperature of the sample from 0°C to 150°C at a temperature rise rate of 10°C / minute in a temperature sweep test using an Advanced Rheometer Expansion System (ARES, TA Instruments) at a frequency of 1 Hz, a strain of 5% and a normal force of 100 N, and measuring the storage modulus at 60°C. The results thereof are shown in Table 1 below and Figure 12 .
[0163] As shown in Table 1 below and Figure 12 , it can be seen that the dry electrode film of the examples exhibited a lower storage modulus at the same measurement temperature compared to the dry electrode film of Comparative Example 1. This means that the degree of fibrillation of the PTFE binder in the dry electrode film increased, and thus, there can be an effect of increasing the tensile strength of the electrode.
[0164] Measurement of tensile strength and sheet resistance of electrode
[0165] Tensile strength and sheet resistance of the electrodes manufactured in the Examples and Comparative Examples were measured. The tensile strength was evaluated using a universal testing machine (UTM, H5KT, Tinius Olsen). The sheet resistance was evaluated using a low resistance meter (Mitsubishi, MCP-T610).
[0166] The results thereof are shown in Table 1 below and Figure 13 Table 1 below and Figure 13 As shown in Table 1 below and
[0167] Table 1
[0168]
[0169] Evaluation of rate capability of the electrodes
[0170] The rate capability of the electrodes of the Examples and Comparative Examples was evaluated by charging at 0.2 C and discharging at 1 C and 2 C, respectively. The results thereof are shown in Figure 14 and 15
[0171] Evaluation of ion resistance according to the application of the electrodes
[0172] The ion resistance of the electrodes of the Examples and Comparative Examples was evaluated, and the ion resistance was evaluated by electrochemical impedance spectroscopy. The results thereof are shown in Figure 16 and 17
[0173] Evaluation of service life according to the application of the electrodes
[0174] Ninety-seven weight% of artificial graphite as a negative active material, 1.5 weight% of carbon nanotube as a conductive additive, and 1.5 weight% of styrene-butadiene rubber were mixed, and water was added to the mixture to prepare a negative electrode slurry.
[0175] The prepared negative electrode slurry was applied to a copper foil, and the negative electrode slurry and the copper foil were dried and calendered to manufacture a negative electrode.
[0176] Using the negative electrode and the positive electrodes manufactured in the Examples and Comparative Examples, using a polyethylene separator (STAR 20, Asahi) as a separator, and using a mixed solvent of ethylene carbonate (EC), methyl ethyl carbonate (EMC), and dimethyl carbonate (DMC) having a volume ratio of 3:3:4 in which 1.15 M LiPF6 is dissolved as an electrolyte, a lithium ion rechargeable battery having a capacity of 2,000 mAh was manufactured.
[0177] The fabricated lithium ion rechargeable battery was charged at 25°C at a constant current of 0.2 C from 2.8 V to an upper voltage of 4.3 V, charged at a constant voltage until the current dropped to 0.05 C (which was a termination condition), and then discharged at 0.33 C until the voltage dropped to a discharge cutoff voltage of 3.0 V. Such a cycle was repeated 50 times. The capacity and efficiency in this case are shown in FIG. Figure 18 As shown in .
[0178] The fabricated lithium ion rechargeable battery was charged at 25°C at a constant current of 0.2 C from 2.8 V to an upper voltage of 4.3 V, charged at a constant voltage until the current dropped to 0.05 C (which was a termination condition), and then discharged at 1 C until the voltage dropped to a discharge cutoff voltage of 3.0 V. Such a cycle was repeated 50 times. The capacity and efficiency in this case are shown in FIG. Figure 19 As shown in .
[0179] like Figure 18 and 19 As shown in , the battery with the electrode of the embodiment exhibited higher capacity and efficiency for the same number of cycles than the battery with the electrode of the comparative example. In addition, the battery with the electrode of Example 1 exhibited higher capacity and efficiency for the same number of cycles than the battery with the electrode of Example 2.
[0180] According to an embodiment of the present invention, an electrode includes a dry electrode film and promotes nanofibrillation of a fibrillable binder, thereby improving mechanical and electrical properties of a battery.
[0181] However, aspects and effects obtainable by the present invention are not limited to the above-described aspects and effects, and those skilled in the art will understand other aspects and technical effects from the description of the present invention provided above.
[0182] Although the present invention has been described above with respect to some example embodiments and drawings, the present invention is not limited thereto, and a person skilled in the art may make various modifications and changes within the technical spirit of the present invention and within the scope equivalent to the scope of the appended claims.
Claims
1. An electrode comprising: a free-standing dry electrode film including an electrode active material, a binder, and a conductive additive, wherein the electrically conductive additive comprises a carbon black-based compound having a specific surface area of 350 m 2 / g or less and a crystallite size of 15 A or more.
2. The electrode of claim 1, wherein the specific surface area of the carbon black-based compound is in the range of 250 m 2 / g to 330 m 2 / g, and the crystallite size of the carbon black-based compound is in the range of 15 A to 16 A.
3. The electrode of claim 1, wherein the carbon black-based compound is graphitized.
4. The electrode of claim 1, wherein a graphitized layer of the carbon black-based compound has a thickness of 1 nm or more.
5. The electrode of claim 1, wherein pores of the carbon black-based compound have a diameter greater than 0 nm and less than or equal to 100 nm.
6. The electrode of claim 1, wherein 80% or more of all pores in the carbon black-based compound include pores having a diameter in a range of 1 to 10 nm.
7. The electrode of claim 1, wherein the carbon black-based compound includes one or more of carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black.
8. The electrode of claim 1, wherein the carbon black-based compound is included in an amount of 90% by weight or more of the conductive additive.
9. The electrode of claim 1, wherein the binder is included in the dry electrode film in a fibrillated state.
10. The electrode of claim 1, wherein the binder includes polytetrafluoroethylene, a polyolefin, or a mixture thereof.
11. The electrode of claim 1, wherein the electrode active material is a positive electrode active material or a negative electrode active material.
12. The electrode of claim 1, wherein the electrode active material includes lithium cobalt oxide.
13. The electrode of claim 1, wherein the carbon black-based compound is prepared by subjecting the carbon black-based compound to flash lamp annealing.
14. The electrode of claim 1, wherein the electrode is an electrode for a rechargeable lithium battery.
15. A rechargeable lithium battery including the electrode of any one of claims 1 to 14.
Citation Information
Patent Citations
Chair Control Apparatus for Electric Wheelchair And Electric Wheelchair Including The Same
KR1020240051523A